(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
ECE is the first level of education in the national education system, laying the initial foundation for children’s physical, cognitive, social, and aesthetic development. Moreover, ECE has equipped children with the full scope of skills for their learning and later success. It is undeniable that teachers play an important role in the education system, especially ECE teachers those who transmit knowledge and shape children’s personalities right from the first days of school. Thereby children form a solid knowledge base and deep roots in their subconscious, providing the basis for all future learning. As can be seen, the tasks of ECE in the national education system in Vietnam are very important, especially in the current period